Enantiospecific formal synthesis of inthomycin C - Athawale, Paresh R.; Kashinath, K.; Reddy, D. Srinivasa (Chemistry Select, 2016)
An enantiospecific synthesis of Hatakeyama's intermediate enynol has been accomplished in both enantiomeric forms. As these intermediates can be converted to (3R)-inthomycin C and (3S)-inthomycin C through respective enynol intermediates using reported procedures, present effort may be regarded as formal synthesis of inthomycin C in both enantiomeric forms. Our synthesis highlights the use of pantolactone chiral pool and thus reconfirms the previously assigned absolute stereochemistry as 3R to the natural product inthomycin C.